(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing technology is a stretchy, price- efficient and provides a nice stand for the trade opportunities and the customer services via network. It is the main route to improve the capacity or else add the capability with dynamism without investing in new infrastructure. From the past few years cloud computing technology was the fastest growing segment in the IT filed. Extreme plenty of information has been stored in the cloud because of its convenience. In the face of of the public relations neighboring in the cloud the consumers are unwilling towards make a proposal for their business in the cloud. The growth of the cloud was deduced by the security issues in the cloud. The complications in the data privacy and the protection of the data will extending due to the clumpness in the market . The cloud architecture have several threatening issues the cloud service users need to be aware of the issues and the existing protective techniques. Hence in this paper a survey was held depends upon the different security issues belongs to the cloud and also its defensive methodology. There are several other existing methodologies are there which can improving the features in the cloud and also reduces the risk in the cloud. This survey was more specific to different safety problems also defensive mechanism in cloud computing.